Prevalence of dry eye disease among indoor and outdoor workers and the impact on work productivity in the West Bank of Palestine in 2024: a cross-sectional study - Sana Khaled Abubaker; Shahd Baker Samaana; Qutaiba Naser Saidi; Jamal A. S. Qaddumi; Hamza Abualhasan; Shahd Ibrahim Abusalha (BMC Public Health)
Abstract Background Dry Eye Disease (DED) is a multifactorial ocular condition characterized by the disturbance of the tear film and interpalpebral ocular surface. It is characterized by ocular itchiness, grittiness, burning, and visual disturbances. Many risk factors were linked to DED, including occupational-related risk factors. This study aimed to investigate the prevalence and impact of DED on work productivity among outdoor and indoor workers in the West Bank of Palestine and the impact of DED on daily activities performance. Methods A population-based descriptive cross-sectional study was conducted on male and female Palestinian workers aged 18 years or older, carried out between July to October 2024. Structured interview questionnaires using the Arabic version of the Ocular Surface Disease Index questionnaire (Arab-OSDI) and the Work Productivity and Activity Impairment questionnaire (WPAI) for participants who scored 13 or higher on OSDI. Results A total of 464 participants were included, ages 18 or older. Males were 81.3% of the study population. 50% of the sample were indoor workers and 50% were outdoor workers. The prevalence of DED in Palestinian workers was 61.4%, which was higher among outdoor workers (64.7%) than indoor workers (58.2%), but this difference was not statistically significant (p = 0.15). The impact of DED on work productivity was reported in all severity levels (p < 0.001); participants with severe DED had a mean of 5.93 h, which is higher than the mean for moderate and mild DED patients (4.71 and 3.42 h), respectively. Similarly, the impact on the ability to perform daily activities was significant (p < 0.001), greatest among respondents with severe disease (5.86 h). Conclusions Outdoor workers have been associated with DED more than in-office workers in the West Bank. Meanwhile, workers with DED report lower productivity and struggle with everyday tasks regardless of the severity level. This underlines the detrimental effects of the workplace on the ocular surface, which present a significant risk for the onset and exacerbation of dry eye symptoms.